Seeing is believing! visualisation of CTA's results - Khadar, Ibrahim (Technical Centre for Agricultural and Rural Cooperation, 2019)
To demonstrate how CTA projects are matching the Centre's corporate targets and to enhance project data integrity, consistency and accuracy, a results data management initiative has been launched.